Molecular Engineering of Trifunctional Supported Catalysts for the Aerobic Oxidation of Alcohols. (19th July 2016) - Fernandes, Antony E.; Riant, Olivier; Jensen, Klavs F.; Jonas, Alain M.
Abstract: We describe a simple and general method for the preparation and molecular engineering of supported trifunctional catalysts and their application in the representative Cu/TEMPO/NMI‐catalyzed aerobic oxidation of benzyl alcohol. The methodology allows in one single step to immobilize, with precise control of surface composition, both pyta, Cu I, TEMPO, and NMI sites on azide‐functionalized silica particles. To optimize the performance of the heterogeneous trifunctional catalysts, synergistic interactions are finely engineered through modulating the degree of freedom of the imidazole site as well as tuning the relative surface composition, leading to catalysts with an activity significantly superior to the corresponding homogeneous catalytic system.